Nuove applicazioni di Realtà Aumentata per il learning by interacting. - Paolo Clini; Emanuele Frontoni; Berta Martini; Ramona Quattrini; Roberto Pierdicca (Archeomatica, 2017)
The adoption of innovative tools and new chains of digitization, represent an unavoidable base of knowledge towards a more clear understanding of our cultural heritage. The article presents a research work conducted for the development of a mobile application, specifically developed according to the paradigm of learning by interacting. The contents of the application, released by Università Politecnica delle Marche for the Galleria Nazionale delle Marche have been scientifically validated by a team of experts of the Gallery; besides, they came from high resolution acquisition, which are the backbone of all the functionalities of the app. Thanks to the monitoring of the user experience and to the standardization of the contents, the application is performing and user centered at the same time. This work paves the way for a multidisciplinary reflection over our digital cultural heritage, and contributes to spread methods and adaptive for the communication, facilitating the adoption by museums and cultural institutions.